Adoption of internet banking theory of the diffusion of innovation - Md Nor, Khalil; Pearson, J. Michael; Ahmad, Altaf (Universiti Utara Malaysia, 2010)
The innovation diffusion theory (IDT) could be considered as one of the earliest theories that attempts to explore factors that influence an individual to adopt an innovation or a new technology. The theory suggests five key beliefs that influence the adoption of any innovation: relative advantage, complexity, compatibility, trialability, and observability. The purpose of this study was to test part of IDT’s attributes empirically. We used Internet banking as the innovation or the targeted technology. We surveyed 1164 business and MBA students in four public universities in Malaysia. Structural equation modelling was used to analyse the data. The results showed that relative advantage, compatibility, and trialability have a significant effect on att itude. Consequently, attitude significantly aff ects the intention to use Internet banking. Based on the findings, implications to practice are offered